A Pot-pourri of debates, dialogue, and a discourse - Thiruchandran, Selvy; Women's Education and Research Centre (Colombo, Sri Lanka) (2013)
Chiefly with reference to Sri Lanka.
Keywords: Women's studies -- Sri Lanka; Women -- Sri Lanka -- Social conditions